2006
DOI: 10.1161/circulationaha.106.644203
|View full text |Cite
|
Sign up to set email alerts
|

Unblinded Pilot Study of Autologous Transplantation of Bone Marrow Mononuclear Cells in Patients With Thromboangiitis Obliterans

Abstract: Background-The short-term clinical benefits of bone marrow mononuclear cell transplantation have been shown in patients with critical limb ischemia. The purpose of this study was to assess the long-term safety and efficacy of bone marrow mononuclear cell transplantation in patients with thromboangiitis obliterans. Methods and Results-Eleven limbs (3 with rest pain and 8 with an ischemic ulcer) of 8 patients were treated by bone marrow mononuclear cell transplantation. The patients were followed up for clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 22 publications
0
95
0
6
Order By: Relevance
“…Many studies using different methods, such as vascular endothelial growth factor (VEGF)‐related gene transfer 6, 7, bone‐marrow mononuclear cell (BMMNC) 8, 9, 10, 11, 12, PBMNC 13, 14, 15, 16, 17, 18, or CD34+ cell 2, 3, 4 transplantation, have been completed and have proven their safety and efficacy. The long‐term outcome after CD34+ cell therapy in CLI patients was already reported by Kinoshita et al in 2012 19.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies using different methods, such as vascular endothelial growth factor (VEGF)‐related gene transfer 6, 7, bone‐marrow mononuclear cell (BMMNC) 8, 9, 10, 11, 12, PBMNC 13, 14, 15, 16, 17, 18, or CD34+ cell 2, 3, 4 transplantation, have been completed and have proven their safety and efficacy. The long‐term outcome after CD34+ cell therapy in CLI patients was already reported by Kinoshita et al in 2012 19.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, clinical results show feasibility and safety (at least in the short term) and indicate an encouraging effect when comparing the patient's status before and after transplantation (Table 1a-c). Noteworthy, however, one study with TAO patients reported a high incidence of adverse effects in the long term (sudden death, worsening of ischemic ulcers or rest pain, development of an arteriovenous shunt) [12], and two other studies (one in patients with a high number of risk factors and one in CTD patients) reported that positive effects may not apply to all patient categories [11,13] (Table 1a-b).…”
Section: Clinical Study Overview and General Trendsmentioning
confidence: 99%
“…Les autres types de cellules souches adultes requièrent une étape d'amplification ex vivo, ce qui impose un délai entre le moment du prélèvement et l'administration des cellules. Une alternative serait de [26,27]. Cependant, un certain nombre de ces patients présentent des effets secondaires, et l'amélio-ration n'est souvent que transitoire [27].…”
Section: Applications Cliniquesunclassified
“…Une alternative serait de [26,27]. Cependant, un certain nombre de ces patients présentent des effets secondaires, et l'amélio-ration n'est souvent que transitoire [27]. De même, la transplantation par voie intracoronaire de cellules mononucléées médullaires dans le myocarde de patients ayant une ischémie aiguë augmente la perfusion et la fonction du tissu ischémié [28][29][30].…”
Section: Applications Cliniquesunclassified